2022
DOI: 10.1155/2022/1972585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Fertilization and Nitrogen Fixing Endophytic Bacteria Supplementation on Soil Fertility, N Uptake, Growth, and Yield of Sesame (Sesamum indicum L.) Cultivated on Alluvial Soil in Dykes

Abstract: The aim of this study was to determine the proper combination of nitrogen (N) fertilizer level and nitrogen fixing endophytic bacteria (NFEB) supplementation for the maximum grain yield of sesame cultivated in alluvial soil in dykes. The experiment followed a completely randomized block design with two factors. The first one was the levels of N fertilizer used, including 0, 50, 75, and 100% N of recommended fertilizer formula (RFF), and the other consisted of no bacteria applied, an individual strain of Entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The capacity of endophytic infection to influence the host growth is dependent on nitrogen levels [48,53,54].Ravel et al [45] and Lewis [55] reported the advantages of endophyte infection at a low nitrogen rate. In sesame, a higher yield was obtained when treated with endophytic bacteria at 25-50% lower fertilization compared to treatment with 100% nitrogen fertilization [56]. However, Cheplick et al [57] reported a significant increase in biomass with endophyte inoculation at intermediate and high nutrient levels but not with low nutrient application [57].…”
Section: Discussionmentioning
confidence: 97%
“…The capacity of endophytic infection to influence the host growth is dependent on nitrogen levels [48,53,54].Ravel et al [45] and Lewis [55] reported the advantages of endophyte infection at a low nitrogen rate. In sesame, a higher yield was obtained when treated with endophytic bacteria at 25-50% lower fertilization compared to treatment with 100% nitrogen fertilization [56]. However, Cheplick et al [57] reported a significant increase in biomass with endophyte inoculation at intermediate and high nutrient levels but not with low nutrient application [57].…”
Section: Discussionmentioning
confidence: 97%
“…The bacterial density was calculated according to the Most Probable Number (MPN) method for PNSB (Harada et al, 2005). The preparation was according to the method used in the study by Thuc et al (2022) with some modifications. In particular, the maize grains were sterilized with 70% ethanol and 1% sodium hypochlorite solution for 3 and 10 min, respectively.…”
Section: Inoculation Of Bacteria On Maize Seedsmentioning
confidence: 99%
“…For instance, the application of organic fertilizers and biofertilizers was able to improve the sesame yield, soil fertility, and seed oil quality with higher contents of oleic, stearic, and palmitic acids, but lower contents of linolenic and linoleic acids [14]. Interestingly, the use of plant growth promoting rhizobacteria (PGPR) processing nitrogen (N) fxing ability and phosphorous (P) solubilization as a biofertilizer could reduce the chemical fertilizer input for sesame [15][16][17] and enhance its N and P uptake [18,19].…”
Section: Introductionmentioning
confidence: 99%